Estimation of the Equilibrium Real Exchange Rate for Malawi - Mathisen, Johan (Washington, D.C. : International Monetary Fund, 2003)
This paper computes Malawi's equilibrium real exchange rate as a function of its fundamentals as derived from economic theory. It finds evidence in favor of the equilibrium approach to exchange rate determination, with several variables (particularly government consumption and real per capita growth) found to drive movements in the time-varying equilibrium real exchange rate. The results also indicate that following a shock there is a rapid reversion of the real exchange rate to its time-varying equilibrium, with a half-life of reversion of about 11 months.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet